ANALISIS HUKUM ATAS PENETAPAN TERSANGKA TINDAK PIDANA KORUPSI DALAM KAITAN DENGAN WEWENANG LEMBAGA PERADILAN (Studi Kasus: Perkara Peradilan Dalam Putusan Pengadilan Negeri Jakarta Selatan Nomor: 04/Pid.Prap/2015/PN.Jkt.Sel.) - Gomgoman Simbolon; Madiasa Albisar; Mahmud Mulyadi; Jelly Leviza (USU LAW JOURNAL, 2016)
ABSTRACT Pre-trial session is one of the efforts to find justice for a litigant. It becomes more popular since the scope of judicial review object as it is stipulated in Article 77 of the Penal Code is not in line with judicial development of law of criminal procedure in eliciting and finding the value of justice. The problem of the research was how about law of criminal procedure which regulates the scope of the authority of pre-trial session and how about the judge’s consideration at the South Jakarta District Court in the Verdict No. 04/Pid.Prap/2015/PN.Jkt.Sel., which decided that the status of defendant in the corruption criminal act was invalid and had no legal ground. The conclusion was that law of criminal procedure, which regulates the scope of the authority of pre-trial session under Article 77 of the Penal Code, cannot be interpreted rigidly and only bound by the valid or invalid arrest, detention, halting the investigation and prosecution, indemnity and rehabilitation, but it should also deal with confiscation, raid, and determining the status of defendant as the object of pre-trial session. The judge’s consideration at the South Jakarta District Court has principally met the purpose of finding justice in determining the object of pre-trial session  because the judge interpreted it broadly by including the confirmation of the status of defendant as the object of pre-trial session. The judge’s decision has also met the principle of legal certainty in determining the subject of corruption offense stipulated in Article 2, figure 7 of Law on Anti Collusion and Nepotism. However, his verdict on the State’s financial damages was principally contrary to the principle of pre-trial session itself because it is part of judicial administration and not a part of pre-trial session Keywords: Pre-Trial Session, Charging Defendant Status, Corruption Criminal Act, The South Jakarta District Court